2013
DOI: 10.2147/dddt.s45575
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine versus haloperidol in the treatment of delirium: a double-blind, randomized, controlled trial

Abstract: BackgroundAtypical antipsychotic drugs may have low propensity to induce extrapyramidal side effects in delirious patients. This study aimed to compare the efficacy and tolerability between quetiapine and haloperidol in controlling delirious behavior.MethodsA 7-day prospective, double-blind, randomized controlled trial was conducted from June 2009 to April 2011 in medically ill patients with delirium. Measures used for daily assessment included the Delirium Rating Scale-revised-98 (DRS-R-98) and total sleep ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
2
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 44 publications
0
75
2
5
Order By: Relevance
“…In addition, polymorphisms within 5-HT 2A receptors have been reported to be associated with schizophrenic patients (Williams et al, 1996;Golimbet et al, 2007;Quednow et al, 2008) or BPSD of AD patients (Pritchard et al, 2008), who frequently exhibit hallucinations, delusions, and psychosis. In delirium, similar to schizophrenia and BPSD, atypical antipsychotic drugs such as olanzapine and quetiapine having a strong 5-HT 2A receptor antagonistic action, are usually used to treat the symptoms including hallucination, delusion, and excitation (Maneeton et al, 2013;Wang et al, 2013;Yoon et al, 2013). In animals, several hallucinogenic compounds such as lysergic acid diethylamide and mescaline, can induce the head-twitch response in normal mice (Corne et al, 1963;Corne and Pickering, 1967) or htr2A þ / þ but not htr2A À / À mice (González-Maeso et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, polymorphisms within 5-HT 2A receptors have been reported to be associated with schizophrenic patients (Williams et al, 1996;Golimbet et al, 2007;Quednow et al, 2008) or BPSD of AD patients (Pritchard et al, 2008), who frequently exhibit hallucinations, delusions, and psychosis. In delirium, similar to schizophrenia and BPSD, atypical antipsychotic drugs such as olanzapine and quetiapine having a strong 5-HT 2A receptor antagonistic action, are usually used to treat the symptoms including hallucination, delusion, and excitation (Maneeton et al, 2013;Wang et al, 2013;Yoon et al, 2013). In animals, several hallucinogenic compounds such as lysergic acid diethylamide and mescaline, can induce the head-twitch response in normal mice (Corne et al, 1963;Corne and Pickering, 1967) or htr2A þ / þ but not htr2A À / À mice (González-Maeso et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Risperidone is also used in the treatment of delirium [57], with comparative efficacy with respect to haloperidol and olanzapine [58] and independent of the severity of the underlying illness [59]. Data have also accumulated on the use of quetiapine [60•], with recent reports indicating a comparable efficacy and safety as haloperidol for controlling delirium symptoms [61] and an increase of its use in general hospital settings [44]. Ziprasidone, a further atypical AP, showed to be as effective as haloperidol in the treatment of delirium in intensive care unit [62], also when used intravenously [63], although no study is available in palliative care settings.…”
Section: Antipsychotics (Aps)mentioning
confidence: 99%
“…Compared to haloperidol, patients with delirium on quetiapine showed similar improvement on the DRS and quetiapine was better tolerated [10]. An open-label trial using quetiapine at a mean dosage of 44.9 ± 31.0 mg/day demonstrated that it was effective and that it improved delirium severity and cognition that were measured by the DRS and MMSE, respectively [22].…”
Section: Discussionmentioning
confidence: 99%
“…Typical antipsychotics, primarily haloperidol, have been used empirically to control symptoms of delirium. Recently, researchers have begun reporting that atypical antipsychotics, such as olanzapine, quetiapine, and risperidone, might be as effective as haloperidol in delirium treatment [10,11,18,19].…”
Section: Discussionmentioning
confidence: 99%